Look Fantasi Dan Style Exotic Dramatic Pada Ready To Wear Dengan Penambahan Hiasan Makrame - Mien Zyahratil Umami; Sindy Aulia Putri (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Ready to wear is ready-to-wear clothing for various occasions with the addition of various interesting variations. One of them is a variation of macrame. Macrame began to be applied to clothing. The problems studied was how the process of making ready-to-wear looks for fantasy and dramatic exotic styles and the application of macrame decorations on clothing. The aim of this report was to know the process of making ready to wear fantasy looks and dramatic exotic styles and the application of macrame decorations to clothing. The method used was R & D. The process of making Ready To Wear includes determining the fashion design, preparing tools and materials, applying measurements, making patterns, cutting materials, marking the stitches on the fabric, ironing upholstery, and sewing clothes. The main materials of this clothes were drill cloth in red, black, white, toyobo fabric in red, black, brown, yellow, and sekar Jagat batik fabric. It used a Japanese anime cartoon fantasy look, Tsundere characters. The style used was Exotic Dramatic Style. The decoration used was macrame. Making macrame was done by hanging it so it did not move. The macrame was made consistently so it did not hang and stretch for too long. The application of macrame to clothing was spread to avoid the spread of macrame. The size of the furing cloth used must be shorter than the main material so that the result was neater.